A Journey to Palmyra : Collected Essays to Remember Delbert R. Hillers - Cussini, Eleonora, (Culture and History of the Ancient Near East ;, 2005)
A Journey to Palmyra originates from the desire to remember Delbert R. Hillers, who greatly contributed with his work to Palmyrene studies. However, it is not meant just as a memorial volume, but as a research tool. It contains thirteen papers by scholars in the field of Palmyrene studies and Semitics focusing on different aspects of Palmyrene history, social history, art, archaeology and philology, with publication of newly discovered inscriptions. It offers a state-of-the-art discussion on several issues pertaining to the field of Palmyrene studies, and illustrates methodologies to be employed in order to increase our knowledge of the complex and multifaceted culture of ancient Palmyra and of neighbouring areas.